Implementation of an organizational intervention to improve low-wage food service workers' safety, health and wellbeing: findings from the Workplace Organizational Health Study - Glorian Sorensen; Susan E. Peters; Karina Nielsen; Elisabeth Stelson; Lorraine M. Wallace; Lisa Burke; Eve M. Nagler; Hamid Roodbari; Melissa Karapanos; Gregory R. Wagner (BMC, 2021)
Abstract Background Many organizational interventions aim to improve working conditions to promote and protect worker safety, health, and well-being. The Workplace Organizational Health Study used process evaluation to examine factors influencing implementation of an organizational intervention. This paper examines the extent to which the intervention was implemented as planned, the dose of intervention implemented, and ways the organizational context hindered or facilitated the implementation of the intervention. Methods This proof-of-concept trial was conducted with a large, multinational company that provides food service through contractual arrangements with corporate clients. The 13-month intervention was launched in five intervention sites in October 2018. We report findings on intervention implementation based on process tracking and qualitative data. Qualitative data from 25 post-intervention interviews and 89 process tracking documents were coded and thematically analyzed. Results Over the 13-month intervention, research team representatives met with site managers monthly to provide consultation and technical assistance on safety and ergonomics, work intensity, and job enrichment. Approximately two-thirds of the planned in-person or phone contacts occurred. We tailored the intervention to each site as we learned more about context, work demands, and relationships. The research team additionally met regularly with senior leadership and district managers, who provided corporate resources and guidance. By assessing the context of the food service setting in which the intervention was situated, we explored factors hindering and facilitating the implementation of the intervention. The financial pressures, competing priorities and the fast-paced work environment placed constraints on site managers' availability and limited the full implementation of the intervention. Conclusions Despite strong support from corporate senior leadership, we encountered barriers in the implementation of the planned intervention at the worksite and district levels. These included financial demands that drove work intensity; turnover of site and district managers disrupting continuity in the implementation of the intervention; and staffing constraints that further increased the work load and pace. Findings underscore the need for ongoing commitment and support from both the parent employer and the host client. Trial registration This study was retrospectively registered with the Clinical Trials. Gov Protocol and Results System on June 2, 2021 with assigned registration number NCT04913168 .